Correlation Between Gender, Physical Activity, Family Obesity History and Consumption of Fruit or Vegetable with Obesity in Medical Students in Surabaya - made sukma putra; Lilik Djuari; Rina Yudiwati (Universitas Airlangga, 2022)
The incidence of obesity in the world has increased recently and doubled from 1980 to 2014. Obesity can increase the risk of many diseases. Medical students are a vulnerable group affected by obesity because of stressful conditions that can increase the incidence of obesity. This analytical research uses a cross sectional method approach using primary data. The populations in this study were medical students at the Faculty of Medicine, Airlangga University. In this study, 300 samples were taken from first-fifth semester students. The independent variables that will be studied in this study are Gender, physical activity, family obesity history, and consumption of fruit or vegetables. The dependent variable in this study is nutritional status. Based on this study found a significant association between gender, family history of obesity, eating of fruits or vegetables to nutritional status. Still, there is no significant association between physical activity on the nutritional group of medical students. Three variables in this research correlated with the nutritional status of medical education students at the Faculty of Medicine, Airlangga University, Surabaya, which are gender, family obesity history, and consumption of fruit or vegetables. From this research, it was found that the incidence of over-nutrition was still high among medical education students and there was still a lack of awareness among students to exercise and consume fruit or vegetables in their meals.